Historic Kyiv Polish. Between North and South Borderlands - Klimek-Grądzka, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article discusses the specific, both sociologically and geographically determined Polish language of Kyiv, perceived by the author as a “territorial variation of the Polish literary language existing within the circle of Polish and Ruthenian intelligentsia in Kyiv in the 17th century around the Kyiv-Mohyla Academy, represented by the prints of the typography of the Kyiv-Pechersk Lavra.” The key was the application of linguistic criteria (phonetic, inflectional and syntactic ones) and answering the question of which variation of the borderland Polish we are dealing with: the northern or the southern one. However, a review of linguistic features shows that the Kyiv Polish language situates itself between the north and south borderlands. At every level of the language, features characteristic of both the southern and northern borderlands are noticeable, with the majority accounting for features common to both regions.